Emotional Labor: Institutional Responsibility and Strategies to Offer Emotional Support for Leaders Engaging in Diversity, Equity, and Inclusion Work - Natsumi Ueda; Adrianna Kezar; Elizabeth Holcombe; Darsella Vigil; Jordan Harper (SAGE Publishing, 2024)
Leaders from marginalized groups disproportionately shoulder emotional labor resulting from the work of diversity, equity, and inclusion (DEI) in higher education. This emotional burden can lead to stress and mental health consequences. Institutions bear the responsibility of addressing the emotional burden. This multiple-case qualitative study aimed to identify effective institutional strategies to alleviate emotional labor. We interviewed 107 leaders at eight institutions to examine their experiences with emotional labor and institutional support. We selected institutions based on their progress toward DEI. Leaders were chosen based on being involved directly in the DEI work within a shared leadership effort. Drawing on Ahmed's theory of diversity work and Zembylas's critical emotional praxis, we identified the following themes: sharing DEI responsibilities with many leaders, creating spaces for emotions, and role-modeling the desired behaviors to build positive relationships and trust. Through these strategies, institutions can reduce emotional labor and create equitable environments for DEI leaders.